Value-based utility broker for jitter management of voice over IP networks - Ibabao, Jhoanna Rhodette Arboleda (2004)
Internet Protocol (IP) is a best-effort technology that does not provide any guarantees on service quality. This lack of reliability poses a great challenge for delivering real-time, interactive applications. In particular, voice has certain requirements that make it highly sensitive to packet loss, delay, and variation in delay (jitter). In oredr to offer Voice over IP (VoIP), a management scheme must be employed in order to maintain the quality at satisfactory levels throughout the duration of the call. A new framework at network management, the Value-Based Utility (VBU) model, uses the knowledge of user satisfaction levels in order to allocate resources more effeiciently. Our research applied the value-based utility model to two scheduling algorithms, Stop-and-Go and Jitter-EDD. We simulated a utility broker managing these schedulers on a single-hop IP network. We injected constant bit rate voice traffic and measured their utilities at the receiver. Our results show that Stop-and-Go with utility can offer tighter jitter bounds than Stop-and-Go alone. Utilities may be applied to Jitter-EDD on a select combination of voice sources, but at the cost of additional complexity to an already complex system.